2002
DOI: 10.1177/000348940211100305
|View full text |Cite
|
Sign up to set email alerts
|

Median Cleft of the Lower Lip: Report of Two New Cases and Review of the Literature

Abstract: Median clefts of the lower lip and mandible are rare craniofacial clefts. Couronné in 1819 was the first to describe the condition. The midline cleft of the lower lip was classified by Tessier as a type 30 craniofacial cleft. Recently, the total number of the reported cases had increased to about 66 in the world literature. In addition, 2 more patients are presented here. The first case involves only a small notch in the vermilion; the deformity was treated by Z-plasty. In the second case, a midline incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
0
23
0
2
Order By: Relevance
“…The Tessier cleft is described as a median cleft from the lower lip to the manubrium sterni, a fissured tongue, an absence of the hyoid bone and a cleft of the manubrium sterni 15,18 . In the present case, the subcutaneous cyst overlying the manubrium sterni in combination with the tongue cleft could warrant the description of a Tessier 30 cleft, although the lower lip is not involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tessier cleft is described as a median cleft from the lower lip to the manubrium sterni, a fissured tongue, an absence of the hyoid bone and a cleft of the manubrium sterni 15,18 . In the present case, the subcutaneous cyst overlying the manubrium sterni in combination with the tongue cleft could warrant the description of a Tessier 30 cleft, although the lower lip is not involved.…”
Section: Discussionmentioning
confidence: 99%
“…Median tongue or lip clefts are described also as being associated with orofacial digital syndromes Type I 8,16,17 , Type II (Mohr syndrome) 8,10,12,14 , Type IV (Mohr-Majewski syndrome) 5,11,14 and Type VI (Varadi syndrome) 14,19 . The midline cleft of the lower lip was classified by Tessier as a Type 30 craniofacial cleft 15,18 . Type 30 clefts show a variation from the lower lip to the suprasternal region 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deformity can range from minor to severe variety and in various combinations. Thus, there may be a midline notch in lower lip to complete midline cleft of the lower lip; associated mandible notching, complete cleft of symphysis of mandible, bifid or absence of tongue, hyoid bone agenesis, thyroid cartilage hypoplasia, strap muscles hypoplasia, bifid or absent manubrium sterni and bifid sternum and ventriculoseptal defect [6]. There may be other associated facial anomalies like cleft of upper lip, cleft palate, Pierre-Robin anomaly, hemifacial microsomia, mucus pits lower lip and dermoid cyst of nose, eye, chin, and ear deformities [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the authors advice corrective surgery of the soft tissue structures at earliest, to avoid feeding and speech abnormality [10,11]. Armstrong and Waterhouse have suggested that reconstruction should be done after the age of 10 years to avoid damaging developing tooth buds years unless there is an emergency like breathing difficulty or feeding problems [6,10]. Mandible surgeries…”
Section: Discussionmentioning
confidence: 99%